2011
DOI: 10.1016/j.jaac.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Screening Parents During Child Evaluations: Exploring Parent and Child Psychopathology in the Same Clinic

Abstract: Objective-Children of depressed and/or anxious parents are at increased risk for developing psychiatric disorders. Little research has focused on screening parents bringing their children for psychiatric evaluation, and few studies have included fathers or Hispanic children. This study aimed to: 1) identify current symptom rates in parents bringing their children for evaluation and 2) determine if parental symptoms were associated with children's symptoms, diagnoses, and functioning.Method-The sample included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 36 publications
3
25
2
1
Order By: Relevance
“…These rates are much higher compared to results from a national comorbidity survey of adults in the general population which reported that 3–5 % of mothers had ADHD and 12.9 % had depression in the past year, although our measures are questionnaire-based [39]. The prevalence of ADHD and depression in mothers in this study is similar and slightly higher to other studies with a sample of children with ADHD or other psychiatric disorders [14, 41, 41]. …”
Section: Discussioncontrasting
confidence: 60%
“…These rates are much higher compared to results from a national comorbidity survey of adults in the general population which reported that 3–5 % of mothers had ADHD and 12.9 % had depression in the past year, although our measures are questionnaire-based [39]. The prevalence of ADHD and depression in mothers in this study is similar and slightly higher to other studies with a sample of children with ADHD or other psychiatric disorders [14, 41, 41]. …”
Section: Discussioncontrasting
confidence: 60%
“…Such interventions could be provided as part of health and mental health care and integrated within treatment services, as public-oriented (e.g., community group work, internet-based or media-based interventions), or as policy-and organization-oriented actions (e.g., capacity building and training; consultation and advocacy; organizational development). In the COPMI literature such conditions/comprehensive approaches are only beginning to emerge (Falkov, 2012;Goodyear et al, 2015;Reedtz, Lauritzen, & van Doesum, 2012;Vidair et al, 2011). …”
Section: Conditions For Developing and Implementing Effective Programsmentioning
confidence: 99%
“…1, 2 Research has consistently shown that maternal depression constitutes an important risk factor for childhood psychiatric illness 1, 3, 4 and negatively influences child psychiatric outcomes, even among treated children. 5, 6 …”
Section: Introductionmentioning
confidence: 99%